2015
DOI: 10.1016/j.ijsu.2014.11.037
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preemptive ropivacaine in inguinal hernioplasty – A randomized controlled trial

Abstract: Preemptive analgesia with 0.75% ropivacaine causes significant reduction in pain perception, request for an analgesic and hospital stay. Therefore it is advisable before inguinal hernioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Several research trials have tested the preemptive analgesic efficacy of various medications and techniques, such as nonsteroidal anti-inflammatory drugs (NSAID), also known as non opioid analgesics [5][6][7]. NSAIDs restrict cyclooxygenase enzymes, leading to inhibition in prostaglandin synthesis.…”
mentioning
confidence: 99%
“…Several research trials have tested the preemptive analgesic efficacy of various medications and techniques, such as nonsteroidal anti-inflammatory drugs (NSAID), also known as non opioid analgesics [5][6][7]. NSAIDs restrict cyclooxygenase enzymes, leading to inhibition in prostaglandin synthesis.…”
mentioning
confidence: 99%
“…Regional anesthetic techniques, such as wound infiltration received by all our study patients, have been shown to be very beneficial [23,24].…”
Section: Discussionmentioning
confidence: 91%
“…6 In contrast (and not surprisingly), when ilioinguinal and iliohypogastric blocks (with 0.75% ropivacaine) were combined with wound infiltration and compared with placebo, there were a number of clinical benefits. 7 Although these reports may oversimplify the concept of pre-emptive analgesia (and the difficulties of any meaningful clinical data), any study that demonstrates a positive effect is worth exploring further. To our knowledge, the present study is the first to look at the use of this common LA solution mixture to provide pre-emptive analgesia in a day-case setting.…”
Section: Discussionmentioning
confidence: 99%